Heart failure quantified by underlying cause and multiple cause of death in Brazil between 2006 and 2016 - Paolo Blanco Villela (BMC, 2021)
Abstract Background The Global Burden of Disease (GBD) does not produce estimates of heart failure (HF) since this condition is considered the common end to several diseases (i.e., garbage code). This study aims to analyze the interactions between underlying and multiple causes of death related to HF in Brazil and its geographic regions, by sex, from 2006 to 2016. Methods Descriptive study of a historical series of death certificates (DCs) related to deaths that occurred in Brazil between 2006 and 2016, including both sexes and all age groups. To identify HF as the underlying cause of death or as a multiple cause of death, we considered the International Classification of Diseases (ICD) code I50 followed by any digit. We evaluated the deaths and constructed graphs by geographic region to compare with national data. Results We included 1,074,038 DCs issued between 2006 and 2016 that included code I50 in Parts I or II of the certificate. The frequency of HF as the multiple cause of death in both sexes was nearly three times higher than the frequency of HF as an underlying cause of death; this observation remained consistent over the years. The Southeast region had the highest number of deaths in all years (about 40,000 records) and approximately double the number in the Northeast region and more than four times the number in the North region. Codes of diseases clinically unrelated to HF, such as diabetes mellitus, chronic obstructive pulmonary disease, and stroke, were mentioned in 3.11, 2.62, and 1.49% of the DCs, respectively. Conclusions When we consider HF as the underlying cause of death, we observed an important underestimation of its impact on mortality, since when analyzed as a multiple cause of death, HF is present in almost three times more deaths recorded in Brazil from 2006 to 2016. The mentioning of conditions with little association with HF at the time of the death highlights the importance of HF as a complex syndrome with multiple components that must be considered in the analysis of mortality trends for implementation of public health management programs.